Earnings Management Persistence and Detection through the Miller Index Evidence from an Emerging Banking Market - Husham Abdul Jaleel Khalaf Al-Taie; Moncef Bouanen Guizani (Celebes Scholar pg, 2026)
This study examines earnings management persistence and detection through the Miller Index using evidence from an emerging banking market. The analysis focuses on the Iraqi Investment Bank over the period 2010 to 2024 and applies a time-based analytical approach to investigate whether deviations in the relationship between working capital adjustments and operating cash flow indicate recurring reporting distortion. The study is motivated by the concern that earnings management should not be understood only as an isolated accounting event, but as a persistent pattern that can weaken the credibility of financial statements and reduce the transparency of reported performance. The findings show that the Miller Index deviates from zero throughout the observed period, indicating repeated instability in the relation between accrual related adjustments and cash generating performance. The results further reveal that the deviations occur in both positive and negative directions, which suggests that reporting intervention is adaptive rather than uniformly income increasing. Additional analysis shows that the magnitude of deviations declines over time, although the pattern does not converge toward full neutrality. These results support the view that earnings management in the sampled bank is persistent and detectable through the interaction between working capital changes and operating cash flow.